The development of personal guidance media using the challenge card game to improve students’ self-acceptance - Nurhidayah Nurhidayah; Muhammad Arifin Ahmad; Kulasse Kanto (Program Studi bimbingan Konseling PPs UNM Makassar, 2021)
This study aims to determine (i) the needs for personal guidance media using the challenge card game to improve self-acceptance of the SMAIT Nurul Fikri Makassar students; (2) the prototype of personal guidance media using the challenge card game to improve self-acceptance of the SMAIT Nurul Fikri Makassar students; and (3) the acceptability of the personal guidance media using the challenge card game to improve self-acceptance of the SMAIT Nurul Fikri Makassar students. This study adopted a research model from Borg & Gall and used interviews and questionnaires for data collection. The results showed that (1) the needs for personal guidance media using the challenge card game to improve self-acceptance of the SMAIT Nurul Fikri Makassar students were high; (2) the prototype of personal guidance media using the challenge card game included challenge cards, worksheets, a guidebook, and self-acceptance reading texts; and (3) the validity and acceptability of the product received moderate-to-high responses from the subject matter expert, the media expert and the guidance and counseling practitioner, while the acceptability of the small group trial of 8 students in grade 12 at SMAIT Nurul Fikri Makassar showed a very high response.